Lumbar intervertebral disc degeneration in professional surfers - Kojima, T.; Kubo, S.; Tajima, N.; Mitsuhashi, R.; Nozaki, S.; Chosa, E. (Sport-Orthopädie - Sport-Traumatologie, 2018)
Background: Surfing was added as an official event of the Tokyo Olympics in 2020. There are many surfers troubled by low back pain, but there is no scientific analysis until now. This time, we took MRI on the lumbar vertebrae in 20 official professional surfers and examined the relationship between the low back pain and the rate of the lumbar disc degeneration. Materials and methods: Subjects are 20 people (16 men, 4 women) of 17 Japan official professional surfers and 3 Japan official professionals bodydoaders in total, average age 29.8 years old (17-57 years), we investigated by use of the lumbar vertebrae T2-weighted magnetic resonance imaging. Results: 11 people (55%) had the low back pain, 10 people (50%)had the lumbar disc degeneration (more than Grade III of Pfirrmann classification), 2 people (10%) had the lumbar spondylolysis. There is no relationship between the low back pain and the rate of the disc degeneration. Conclusions: The prevalence rate of low back pain in the professional surfers was approximately equal to previous report. The prevalence rate of the lumbar disc degeneration was 50%, and it was not high rate particularly in comparison with baseball and the swimming. The surfing competition is easy to cause the low back pain, but is not easy to cause the disc degeneration.